Stop motion - Purves, Barry (Basics animation, 2010)
Teaches the skills required to develop as a creative stop-motion animator or articulated puppet maker. This book explores how all the elements of film-making camera work, design, colour, lighting, editing, music and storytelling come together in this art form. It is useful to students who learn to use and exploit the particular types of movement.